APPOINTMENT OF HANDWRITING EXAMINATION: ANALYSIS OF COURT PRACTICE - Veronika N. Shkabaro; Аlona V. Bila; Vladislav V. Voronin (Alfred Nobel University Journal of Law)
The article is devoted to the study of the peculiarities of the appointment of handwriting examination in civil proceedings based on the analysis of court practice. The scientific work describes the procedure for appointing handwriting expertise in civil proceedings. The role of handwriting examination in establishing the truth in the case is determined. The authors indicate that the analysis of court practice gives grounds for asserting that, for the most part, courts take into account the expert's decision based on the results of the handwriting examination as a means of proof and consider it a valid piece of evidence in the case. It is noted that the expert's decision, like any other evidence, may be questionable or even incorrect for various reasons, in particular, the expert may be presented with incorrect initial data or invalid objects. Attention is focused on the role of the judge in the process of preparing for the examination, in particular, the collection of materials for expert research, the judicial practice regarding the consideration of cases in which a handwriting examination was appointed and evaluated by the court, including court decisions in civil cases, decisions on appointment is analyzed expertise, decisions of appeal courts, as well as the Supreme Court and the European Court of Human Rights. Based on the results of the analysis of court practice, the authors made conclusions, including: 1) an expert's decision is evidence in a civil trial; 2) the court must provide a well-founded motivation for rejecting the expert's decision in the case of failure to provide its assessment, because it is not enough in the decision to indicate certain doubts about the reliability or correctness of the expert's decision, without noting at the same time reasonable grounds for such doubts; 3) the courts take into account the expert's decision based on the results of the handwriting examination as a means of proof and consider it a valid evidence in the case, but there are exceptions; 4) the court decision on the appointment of an expert must necessarily specify the questions that are put to the expert for research; 5) the party in the case has the right to object to the handwriting examination; 6) there are cases of the impossibility of conducting a handwriting examination at the stage of its conduct due to non-payment of experts' services; 7) the most common civil cases, within the scope of which an expert's decision is evaluated as a means of proof, are cases of invalidating a will, collection of funds under a loan agreement and receipt, invalidation of land lease agreements, etc.